Meanings of ‘Tuberculosis’ in Rural Indigenous Communities from a Municipality in the Colombian Amazon - Muñoz Sánchez, Alba Idaly; Rubiano Mesa, Yurian Lida (Investigación y Educación en Enfermería, 2017)
Objective. The purpose herein was to describe the meanings on tuberculosis (TB) in rural indigenous communities from a municipality in the Colombian Amazon. Methods. This was an ethnographic study with theoretical reference of dialectical hermeneutics, which created focus groups, one for each rural community of Puerto Nariño, for a total of 15 focus groups. The participants were community leaders and health referents. Results. Seventy-nine subjects participated, mostly midwives, kurakas, traditional physicians, and shamans. The analysis yielded four categories: knowledge of TB, attitudes regarding TB, community practices of TB, and the intervention proposal on TB by the participants. It was found that community leaders recognize TB as a disease that can cause death, but which can be cured if timely care is secured. The study also identified the need to conjugate western medicine with traditional medicine. Conclusion. It is recognized that meanings may impact upon knowledge, attitudes, and practices that affect early detection and treatment of the disease. In addition, this work corroborates the need to strengthen and develop educational programs on tuberculosis supported by the real needs of the communities to enhance their knowledge, attitudes, and practices on the disease How to cite this article: Muñoz AI, Rubiano YL. Meanings of ‘Tuberculosis’ in Rural Indigenous Communities from a Municipality in the Colombian Amazon. Invest. Educ. Enferm. 2017; 35(2): 165-173.